3GPP: LTE- AN INNOVATIVE TECHNOLOGY TOWARDS 4G WIRELESS NETWORKS - J Vijay Franklin; K. Paramasivam (European Scientific Journal, ESJ, 2013)
3GPP: LTE –Long term evolution is baseline to the modern 4th generation communication technology, that is an enhanced version of Universal Mobile Telecommunication System (3G). LTE is introduced by 3GPP.LTE is standardized in the form of REL-8, this is operated in data rate 100 Mbps for downlink and 50 Mbps for uplink in the 20 MHz bandwidth. LTE can accommodate up to 200 users in cell (5 MHz). The objective of LTE is to reduce costs, providing high performance, enhances the features, improves the data transfer speed, and reduce resource utilization. The main advantages are it provides end –to-end Qos, Enhanced multimedia broadcast service, spectrum flexibility. It uses OFDM for modulation. In OFDM a large no of sub carriers are used to convey the data. Each and every sub carrier carries one data. Data will be split into no of data streams. And also it uses SCFDMA, for single carrier modulation. For downlink LTE uses OFDMA with CP. MIMO (multipleinput Multiple-output) is an antenna technology used to improve the performance of communication. In this multiple antenna are used to send and receive multiple data streams. LTE uses a new resource scheduling algorithm called multi carrier channel dependent resource scheduling